Soviet research on crystal channeling of charged particle beams - Kassel, Simon; Rand eBooks (Santa Monica, CA : RAND, 1985)
This report presents an overview of Soviet research in charged particle beam channeling in crystals from 1972 to the present, and the resulting electromagnetic emission, including Soviet proposals for channeling emission lasers in the x-ray region of the spectrum. It analyzes Soviet attitudes toward crystal channeling of charged particles as a subject of research, describes performers of the research, and indicates the level of effort involved. It presents a brief history of crystal channeling research, the differences between channeling and other kinds of electromagnetic radiation, the definition of the main research issues, and estimates of the potential capabilities of channeling radiation, all based on the Soviet viewpoint. It then describes Soviet proposals for laser systems utilizing the channeling radiation mechanism, and analyzes Soviet experimental work involving the observation and measurement of channeling radiation. The author concludes that the outstanding feature of Soviet research in this area is the optimistic belief of Soviet specialists in the technological potential of this research, but finds that the role of the laser proposals in Soviet planning is ambiguous.
"March 1985."
This research was conducted under RAND's National Defense Research Institute.
Includes bibliographical references (p. 41-45).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Channeling (Physics) -- Research -- Soviet Union; Crystals -- Effect of radiation on -- Research -- Soviet Union; Lasers -- Research -- Soviet Union; Particle beams -- Research -- Soviet Union; Electronic books